(untitled) (International Journal of Tissue Repair, 2025)
In August 2025, a national meeting was held in Washington, D.C., gathering 32 experts from across clinical, academic, manufacturing, legal and policy sectors to address the clinical, regulatory, and economic landscape of CAMPs. This consensus document summarizes key discussions from that meeting and the panel recommendations are aimed at improving the regulatory and reimbursement environment for CAMPs in the U.S., while concurrently ensuring Medicare beneficiaries have equitable access to advanced therapies for wound healing and amputation avoidance.